Protein synthesis, cell division and cell death - Davidoff, Avri Nava (My University, 1993)
In this study the morphologic, cytokinetic, biochemical, and molecu1w: consequences of low-dose continuous Puromycin-exposure were examined in HL-60 cells, and in a variety of malignant and non-malignant human and murine cell types. Puromycin (PM) is a composite of the amino nucleoside dimethyladenosine and tyrosine-o-methylether. Functionally it is an analogue of the terminal aminoacyl-adenosine portion of aminoacyl-tRNA, more specifically of tyrosyl..tRNA. At high concentrations 5-S0#tg/ml (10-100#tM) PM has been found to block protein synthesis completely by causing the premature release from the ribosomes of truncated peptide chains which are bound to PM through their carboxyl termini. The nascent PMGpeptide complexes (PMPs) are rapidly degraded through a ubiquitin-dependent pathway and are of interest because of (i) their potential to compete for degradation with the natural substrates of the ubiquitin-dependent pathway, including cyclin B, and (ii) because their structure predicts an inhibitory effect on tyrosine kinase activity. In the current' study then, special consideration was given to the effect of PM on the cell cycle, on apoptosis (programmed. cell death), and on tyrosine kinase activity, As a means of comparison, certain of these effects were also examined with respect to another translation inhibitor Cycloheximide (CHX), to two other substituted purines Puromycin Amino nucleoside (PAN) and 6..Dimethylaminopurine (6-DMAP), as well as to the cyclophospbamide derivative Mafosfamide (ASTA Z 7557).
A thesis submitted to the Faculty of Science, University of Witwatersrand, Johannesburg, South Africa, in fulfilment of the requirements for the Degree of Doctor of Philosophy, This thesis presented as a series of manuscripts 1993
Keywords: Proteins--Synthesis; Puromycin; Cytokinesis; Cell cycle; Cell division